2011
DOI: 10.1007/s10566-011-9165-3
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of the Use of Restraint and Seclusion in a Special Education School

Abstract: Background The literature regarding the use of restraint and seclusion in schools is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…They found that younger students were more likely than high school students to be restrained or secluded, which is consistent with the findings of several reports that age is correlated with the implementation of restraint and seclusion procedures (Child Welfare League of America, 2004;Leidy, Haugaard, Nunno, & Kwartner, 2006). Also, crisis episodes requiring intervention for the high school students were less frequent, but slightly longer in duration for both restraint and seclusion (Villani et al, 2012).…”
Section: Documentation Of Usesupporting
confidence: 86%
“…They found that younger students were more likely than high school students to be restrained or secluded, which is consistent with the findings of several reports that age is correlated with the implementation of restraint and seclusion procedures (Child Welfare League of America, 2004;Leidy, Haugaard, Nunno, & Kwartner, 2006). Also, crisis episodes requiring intervention for the high school students were less frequent, but slightly longer in duration for both restraint and seclusion (Villani et al, 2012).…”
Section: Documentation Of Usesupporting
confidence: 86%
“…Restraint (i.e., physical restriction, including by devices or equipment, that causes immobilization or a reduction in ability to move torso, arms, legs, or head) and seclusion (i.e., involuntary, solitary confinement accompanied by physical prevention from leaving confinement) practices often are used with students who present challenging behaviors that place themselves or others at risk (Persi & Pasquali, 1999; Ryan et al, 2009). In the past, restrictive practices were widely used with students with disabilities (Ryan, Peterson, & Rozalski, 2007; Villani, Parsons, Church, & Beetar, 2012) and young children (Ryan et al, 2007). Past research (Persi & Pasquali, 1999; Ryan & Peterson, 2004) and reports (The Council of Parent Attorneys and Advocates, Inc. [COPAA], 2009; GAO, 2009) reveal that many students have been victims to the use of restraint, seclusion, and/or other aversive techniques in schools, despite increased implementation of school-wide positive behavioral interventions and supports (SW-PBIS).…”
mentioning
confidence: 99%
“…Second, the use of these measures was more frequent in the age group from 6 to 9 years, signifying the elevated use of coercive measures at the beginning of the children's school career. Previous studies have also reported the elevated use of restriction and seclusion during the first school years in comparison with the later phases either as crisis management tools (Villani et al 2012) or as coercive measures (Westling et al 2010). This figure may indicate that children with disabilities present more frequently with challenging behaviour during their early years of schooling, rather than later.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have also reported the elevated use of restriction and seclusion during the first school years in comparison with the later phases either as crisis management tools (Villani et al . ) or as coercive measures (Westling et al . ).…”
Section: Discussionmentioning
confidence: 99%